Transcultural Zen design frameworks for enhancing mental health through restorative spaces and user experience - Yan Jia; Muhammad Firzan Abdul Aziz; Rongrong Sun (Scientific Reports)
Abstract Zen aesthetics, rooted in Chinese Chan Buddhist philosophy, offers a universal framework for designing restorative spaces that transcend cultural boundaries. This study investigates how Zen principles—simplicity, natural harmony, spatial balance, and negative space—are adapted in tea room design across diverse cultural contexts and evaluates their impact on user experience. Through semi-structured focus group discussions with eight expert designers from East and Southeast Asia, complemented by case studies of Zen-inspired spaces in Europe and Scandinavia, the research identifies key strategies for balancing cultural authenticity with global applicability. Findings reveal that minimalist layouts, biophilic integration, and strategic use of negative space reduce self-reported stress by 22–35% and enhance cognitive focus, aligning with established stress recovery and attention restoration theories. Designers achieved cultural hybridity through material substitution, such as Nordic wool felt replacing traditional tatami mats, and ritual adaptation, such as reimagining tea ceremonies as barista-led pour-over rituals, while maintaining Zen’s philosophical core. The study advances a transcultural design framework that prioritizes locally sourced materials, modular spatial configurations, and participatory methodologies to address urban mental health challenges. By bridging Zen philosophy with evidence-based design practices, this work provides actionable insights for creating culturally resonant yet globally adaptable restorative environments in an interconnected world.